Expropriation for Reasons of Public Utility: Array - Ieremie, Maria Cristiana (Journal of Danubian Studies and Research, 2021)
In Romania, before the events that led to the overthrow of the communist political regime, Antonie Iorgovan considered that the goods in respect of which the state administration bodies hold the right of administration for public use, form the public domain. Expropriation for reasons of public utility is a set of administrative and jurisdictional acts and operations, by which the state or local public administration authorities impose the forced transfer, for their benefit, of ownership of real estate belonging to individuals or legal entities with or without profit , as well as those in the private property of communes, cities, municipalities and counties, for the purpose of public utility and in exchange for a fair and prior allowance.